CaFiAR: Software to Learn Fish Cultivation in the Bucket to Support Food Security Program in Society - Rahmalia Syahputri; Muhammad Alifiya; Nurfiana Nurfiana; Jaka Darmawan (Prosiding International conference on Information Technology and Business (ICITB), 2021)
Budikdamber is a method of cultivating fish and vegetables in the bucket to support food security in the community. This cultivation is easy to install, cheap, and suitable for narrow areas or limited water. This technique is implemented in various community groups; however, many of them are facing difficulties because of a lack of information and experiences. To overcome this issue, an application, CaFiAR, based on augmented reality technology was built to bestow information of 3D pictures of ready to harvest and sick catfish. The 3D objects were developed using Blender and Android Studio software. After several tests, we found this application behaving according to its framework and acceptable among the cultivator.Keywords—software, fish, cultivation, food, security,orphanage